Exploring the effect of aeration intensity on a modified PVDF-PEG membrane incorporated with nano-MgO: antifouling and AnT-POME treatment - Man, Hasfalina Che; Abdulsalam, Mohammed; Ahmad Abdullahi, Fikri; Marlina Abd-Karim, Murni; Faezah Yunos, Khairul; Aida Isma, M.I (Taylor & Francis Group, 2023)
Aeration effects on membrane filtration of wastewater remain partially explored, as lesser or excessive application often aggravates the fouling. Furthermore, most polymeric membranes are hydrophobic, which facilitates the deposition of foulants and layer formation. There is a need for further investigation on the use of aeration and membrane modifications with a better antifouling property. This study focused on investigating the influence of aeration intensity on the antifouling performance of a modified co-polymerized polyvinylidene-fluoride (PVDF-PEG) fiber using a hydrophilic nano-MgO to treat anaerobically digested palm oil mill effluent (AnT-POME). The aeration intensity was varied to three levels (3,4,5Lmin-1). Both neat and modified membranes obtained their best AnT-POME permeate flux at 4Lmin-1 with a relatively stable value of 28.67 and 89.85 Lm-2 h-1 after 5 h filtration, respectively. The irreversible fouling percentage (IFP) for the neat and modified membrane at 4Lmin-1 aeration intensity, was 66.67 and 12.42, respectively. This indicates that the neat membrane is more susceptible to fouling. To investigate the changes in the membranes, the fouled membranes were characterized using SEM, FTIR and porosity, then compared with that of the pristine samples. Cake-scaly layers were noticed on the neat membrane. Additionally, both membranes successfully reduced the COD, TDS, TSS, and TN above 60%.